Skrinning Fitokimia Pandanus julianetii Sebagai Sumber Pangan Fungsional Lokal Papua - Condro, Novita (Jurnal Ilmu Pangan dan Hasil Pertanian, 2020)
Pandanus julianetii or the local name is tuke, also called kelapa hutan is a commodity plant in the Papua Mountain area and has long been used by local people as food. This aims to identify bioactive compounds through phytochemical screening in extraction to find out and study the potential of Pandanus julianetii as a local functional food of Papua. Raw Pandanus julianetii was obtained from Yahukimo District. Pandanus julianetii used three treatments namely raw, burned, and smoked. Furthermore, the stages of sample preparation are made into powder and extracted. Phytochemical screening analysis includes alkaloid, flavanoid,and tannin tests. Phytochemical screening resulted showed that Pandanus julianetii contains flavonoids, alkaloids, saponins and tannins which are bioactive components and have functional properties.